Additively manufactured CrMnFeCoNi/AlCoCrFeNiTi0.5 laminated high-entropy alloy with enhanced strength-plasticity synergy. (1st July 2020) - Guan, S.; Wan, D.; Solberg, K.; Berto, F.; Welo, T.; Yue, T.M.; Chan, K.C.
Abstract: In this study, we additively manufactured a CrMnFeCoNi/AlCoCrFeNiTi0.5 laminated high-entropy alloy (HEA), with alternating layers of both constituent materials, that exhibits enhanced strength-plasticity synergy during compression (yield strength up to 990 MPa and no complete fracture until 80% strain), surpassing those of monolithic bulk HEAs. The enhanced strength-plasticity synergy originates from heterogenous microstructures of ultra-hard body-centered-cubic equiaxed grains and soft face-centered-cubic columnar grains periodically arranged in the AlCoCrFeNiTi0.5 and CrMnFeCoNi lamellae, respectively. This study demonstrates a feasible and flexible way to design HEAs with heterogenous microstructures and superior mechanical properties. Graphical abstract: Image, graphical abstract